Engineering geological methods applied in mountain road survey - an example from Baitadi-Darchula road project (Nepal) - Dhital, M. R.; Upreti, B. N.; Dangol, V.; Bhandari, A. N.; Bhattarai, T. N. (Journal of Nepal Geological Society, 1991)
Engineering geological studies were carried out for the Baitadi -Darchula Road in prefeasibility, feasibility, and detailed design stages. Methodology, application, and results from each stage are presented together with the geology and geomorphology of the region.